Lagothrix flavicauda (Primates: Atelidae). (11th October 2021) - Serrano-Villavicencio, José E; Shanee, Sam; Pacheco, Víctor
Abstract: Lagothrix flavicauda (Humboldt, 1812), commonly known as the yellow-tailed woolly monkey, is one of the largest New World primates. Its diet is based on fruits and leaves, and occasionally flowers, buds, epiphyte roots, invertebrates, and some vertebrates. It is endemic to the cloud forests of northern Peru, in Amazonas, San Martín, Huánuco, Junín, La Libertad, and Loreto departments at elevations from 1, 000 to 2, 800 m. It lives in groups of up to 30 individuals. Lagothrix flavicauda is listed as "Critically Endangered" (CR) by both the International Union for Conservation of Nature (IUCN) and under Peruvian legislation, and on Appendix I of the Convention on International Trade in Endangered Species of Wild Fauna and Flora (CITES).